TRIZ as innovation management tool: insights from academic literature. (2017) - Teplov, Roman; Chechurin, Leonid; Podmetina, Daria
A toolkit of methods assisting creativity and inventive thinking called 'theory of inventive problem solving' (TRIZ in Russian or TIPS in English transcription) has numerous successful practical applications both in manufacturing engineering and services. However, the evidence of TRIZ application in innovation management is limited. To fill this gap, this paper presents a systematic literature review of academic articles discussing TRIZ-based innovation methodologies. Our findings reveal that such elements of TRIZ, like contradiction analysis and the trends of engineering system evolution, are most commonly applied in innovation management, particularly on the ideation stages. Also, TRIZ tools demonstrate good complementarity with QFD1-based methodologies. Additionally, to the benefits of TRIZ tools, the results of our study confirmed the subjectivity of solutions and dependence on prior user experience. The application of TRIZ methodology for stimulating innovation process in SMEs is rather rare.